2019
DOI: 10.2147/hiv.s216093
|View full text |Cite
|
Sign up to set email alerts
|

<p>Strategies To Improve Linkage To HIV Care In Urban Areas Of Sub-Saharan Africa: A Systematic Review</p>

Abstract: Of the 37 million people estimated to be living with HIV globally in 2017, about 24.7 million were in the sub-Saharan Africa region, which has been and remains worst affected by the epidemic. Enrolment of newly diagnosed individuals into care in the region, however, remains poor with up to 54% not being linked to care. Linkage to care is a very important step in the HIV cascade as it is the precursor to initiating antiretroviral therapy (ART), retention in care, and viral suppression. A systematic review was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Participants in the current study reported using referral for linking participants to post-trial care which they considered passive and unreliable in facilitating successful linkage. Although established international research institutions (Rennie & Sugarman, 2009; UNAIDS, 2012; UNCST, 2014) consider referral as an acceptable approach to post-trial care, this approach has been criticised by various authors who confirm this study’s finding that a more practical, proactive and staff-facilitated approach to HIV care linkage is required (Koduah Owusu, Adu-Gyamfi, & Ahmed, 2019). A more proactive approach has been successfully used to link HIV positive individuals to care following HIV testing and research has demonstrated higher rates of linkage to, and retention in, HIV care (Elul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in the current study reported using referral for linking participants to post-trial care which they considered passive and unreliable in facilitating successful linkage. Although established international research institutions (Rennie & Sugarman, 2009; UNAIDS, 2012; UNCST, 2014) consider referral as an acceptable approach to post-trial care, this approach has been criticised by various authors who confirm this study’s finding that a more practical, proactive and staff-facilitated approach to HIV care linkage is required (Koduah Owusu, Adu-Gyamfi, & Ahmed, 2019). A more proactive approach has been successfully used to link HIV positive individuals to care following HIV testing and research has demonstrated higher rates of linkage to, and retention in, HIV care (Elul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach could be adapted for HIV trial closure. Currently, data on linkage to care following research participation is lacking (Koduah Owusu et al, 2019) and this is an important research gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Client linkage to care and treatment initiation . For the purposes of the study, successful linkage to care followed the Centers for Disease Control and Prevention (CDC) definition of, a newly-identified HIV-infected person engaging with a health care provider within 30 days of diagnosis (at the ZAZI HTS centre) [ 16 ]. This definition was adopted for linkage to care for all conditions–communicable and NCDs, alike–and for successful treatment initiation , which was additionally defined as an initiation of pharmacological treatment within 30 days of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Active referral is a more facilitated approach, assisting the patient to remain engaged within the healthcare system, and in this context, reach care and initiate treatment. A systematic review of literature aiming to increase linkage of PLHIV among urban areas of SSA to care and treatment reported four common, active approaches: health system interventions, patient convenience and accessibility, behaviour-related interventions and peer support, and incentives [ 16 ]. These active referral methods combat different patient barriers to care and treatment (i.e.…”
Section: Introductionmentioning
confidence: 99%